2002
DOI: 10.1007/s11663-002-0063-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the continuous casting of steel—past, present, and future

Abstract: This lecture honoring Keith Brimacombe looks over the history, current abilities, and future potential of mathematical models to improve understanding and to help solve practical problems in the continuous casting of steel. Early finite-difference models of solidification, which were pioneered by Keith Brimacombe and his students, form the basis for the online dynamic models used to control spray water flow in a modern slab caster. Computational thermal-stress models, also pioneered by Brimacombe, have led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 29 publications
(45 reference statements)
1
103
0
Order By: Relevance
“…[32] The mold walls are routinely tapered to match the steel shrinkage in order to minimize air gap formation and to facilitate primary cooling. [34] It is estimated that primary cooling during continuous casting of steel in the mold removes about 40 pct of the total superheat and about 30 pct of the total sensible heat. [11] The surface heat-transfer coefficient typically decreases down the length of the mold from a peak value of 1500 to 2000 W m Ϫ2 K Ϫ1 at the meniscus to about 600 to 800 W m Ϫ2 K Ϫ1 [22] near the mold bottom.…”
Section: A Mold (Or Primary) Coolingmentioning
confidence: 99%
“…[32] The mold walls are routinely tapered to match the steel shrinkage in order to minimize air gap formation and to facilitate primary cooling. [34] It is estimated that primary cooling during continuous casting of steel in the mold removes about 40 pct of the total superheat and about 30 pct of the total sensible heat. [11] The surface heat-transfer coefficient typically decreases down the length of the mold from a peak value of 1500 to 2000 W m Ϫ2 K Ϫ1 at the meniscus to about 600 to 800 W m Ϫ2 K Ϫ1 [22] near the mold bottom.…”
Section: A Mold (Or Primary) Coolingmentioning
confidence: 99%
“…For the four mentioned models, Kozlowski et al [38] suggested various constitutive relations for p   as functions of stress, temperature, carbon content, activation energy, and various adjustable parameters such as temperature dependent stress exponent, etc. (see also Thomas [99,100] for a review of this subject). In the continuous casting of steel, when mold powder is added to the free surface of the liquid steel, it begins to melt and flow.…”
Section: A Brief Review Of Various Viscosity Modelsmentioning
confidence: 99%
“…The secondary cooling zone has the role to continue the wire cooling after it has emerged from the crystallizing and to assure the total solidification of the semi-product. It is considered "the heart" of a continuous casting and has the role of ensuring the quality of the material, the material surface shape and has to ensure a homogeneous cooling and a uniform repartition of the water on the materials surface [4].…”
Section: Introductionmentioning
confidence: 99%